A fungal chromatin remodeler drives transcription by establishing an open chromatin architecture and activated histone environment - Mengting Xu; Qi Zhang; Yuan Li; Wei Zhou; Lingyun Lei; Fucheng Lin; Yanjun Kou; Zeng Tao (Cell Reports)
Summary: Chromatin remodelers are central regulators of chromatin architecture and transcriptional dynamics, yet the mechanisms underlying the establishment of transcriptionally permissive chromatin and an activated histone environment remain elusive. In the filamentous fungus Magnaporthe oryzae, we demonstrate that remodeling the structure of chromatin 1 (RSC1) functions as a critical regulator in this process. RSC1 is indispensable for establishing open chromatin architecture, and its activity is tightly correlated with altered nucleosome occupancy. Mechanistically, RSC1 physically associates with a H3K27me3 demethylase and positively modulates its abundance, thereby establishing precise chromatin boundaries to restrict heterochromatin spreading. Additionally, RSC1 recognizes histone acetylation and recruits histone acetyltransferase, which synergistically drive histone hyperacetylation at its targets. By integrating a chromatin remodeling complex, H3K27 demethylation, and histone hyperacetylation, RSC1 orchestrates an activated histone environment to promote transcriptional permissiveness. Collectively, these findings elucidate pivotal roles of RSC1 in counteracting facultative heterochromatin formation, enhancing chromatin accessibility, and activating gene expression in fungi.